2019
DOI: 10.1371/journal.pone.0217980
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with treatment type of non-malarial febrile illnesses in under-fives at Kenyatta National Hospital in Nairobi, Kenya

Abstract: Background Non-malarial febrile illnesses comprise of almost half of all fever presenting morbidities, among under-five children in sub-Saharan Africa. Studies have reported cases of prescription of antimalarial medications to these febrile under-fives who were negative for malaria. The treatment of these children with antimalarial medications increases incidences of antimalarial drug resistance as well as further morbidities and mortalities, due to failure to treat the actual underlying causes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 22 publications
1
13
0
Order By: Relevance
“…In Kenya, two acute cases of Sindbis virus were detected by inoculation on Vero cell lines and RT-PCR in febrile patients from Mfangano islands of Lake Victoria [ 47 ], and seroprevalence studies in other Kenyan regions have shown exposure in local populations [ 48 , 49 ]. Clinical cases may be masked by other febrile illnesses, such as malaria in Kenya, and may therefore go unnoticed due to lack of awareness and inadequate diagnostic capabilities in health institutions [ 12 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, two acute cases of Sindbis virus were detected by inoculation on Vero cell lines and RT-PCR in febrile patients from Mfangano islands of Lake Victoria [ 47 ], and seroprevalence studies in other Kenyan regions have shown exposure in local populations [ 48 , 49 ]. Clinical cases may be masked by other febrile illnesses, such as malaria in Kenya, and may therefore go unnoticed due to lack of awareness and inadequate diagnostic capabilities in health institutions [ 12 , 50 , 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…If laboratory performance percent confirmed declines it means; laboratory performance was decreasing over the years or something causing febrile illness in the area is increasing. Misdiagnosis and treating malaria clinically based only on fever with antimalarial drugs, which is still in remote settings, may contribute to the rapid emergence of antimalarial drug resistance [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…If laboratory performance percent con rmed declines it means; laboratory performance was decreasing over the years or something causing febrile illness in the area is increasing. Misdiagnosis and incorrect treatment of such non-malarial febrile illnesses with antimalarial drugs is possibly to contribute to rapid emergence of antimalarial drug resistance [21,22] in the study area.…”
Section: Discussionmentioning
confidence: 99%